A Literature Review on Stress and Eating Disorders in Adolescents: Psychological and Behavioral Perspectives - Deviantony, Fitrio; Gani, Amelinda Nasywa Filial; Hariyanti, Fajar Dini; Adzahri, Hasbi Asyidiq (Journal of Rural Community Nursing Practice, 2025)
Background: Stress affects adolescent health, often leading to unhealthy eating and increasing the risk of eating disorders, especially in young women. Academic pressures and body image concerns intensify stress-related eating. Interventions like mindfulness and nutrition education can support healthier coping and reduce eating disorders in youth. Purpose: The study aims to highlight the significant impact that stress can have on eating behaviors and to provide insights into how these factors are interconnected. Methods: A review of the literature from 2019 to 2024 was conducted as part of this research technique using PubMed and Science Direct, the keywords "stress level," "eating disorder," and "adolescent". Results: The literature review found a significant association between high-stress levels and the prevalence of eating disorders in adolescents, highlighting the need for targeted interventions to address this issue. Conclusions: Beyond merely reiterating the observed correlation, this review emphasizes the urgent necessity for integrated approaches that combine stress management techniques with nutritional education in school settings. Practical implications include the development of school-based programs that incorporate mindfulness training, cognitive behavioral therapy (CBT) principles, and workshops on healthy eating habits. Furthermore, early identification and intervention strategies, such as routine mental health screenings and accessible counseling services, are crucial to mitigate the long-term impact of stress-induced eating disorders.